Interface stable electrolyte for high-nickel silicon-based battery and application thereof
Patent Information
- Application Number
- CN202611308654.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明公开了一种用于高镍/硅基电池的界面稳定型电解液及其应用,属于锂离子电池电解液技术领域;解决高镍/硅基电池体系中因水分引发的HF腐蚀与界面不稳定问题,提升电池循环性能与安全性
[0016]本发明产生的有益的技术效果为:本发明采用硅基化合物添加剂,可有效捕获电解液微量水分与HF,抑制锂盐水解副反应与酸性腐蚀,此物质也易于在电极表面形成稳定界面膜,不仅抑制高镍正极金属溶出,还能抑制因硅负极膨胀导致界面保护膜的破损,提升电池循环稳定性与安全性;硅基添加剂与羧酸酯溶剂协同效应优异,可抑制羧酸酯高压氧化分解,保留其高电导率优势,兼顾电池快充性能与电解液高压稳定性;环状碳酸酯构建稳定锂盐溶剂化结构,硅基添加剂可协同优化体系界面环境,拓宽电解液电化学窗口,提升热稳定性,适配高镍/硅基电池高压、宽温域工作场景;
Smart Images

Figure SMS_10 
Figure SMS_11 
Figure SMS_12
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery electrolyte technology, specifically to an interface-stabilized electrolyte for high-nickel silicon-based batteries and its application. Background Technology
[0002] High-energy-density batteries, using nickel-rich cathodes and silicon-based anodes, both face the challenge of electrolyte interface instability. The core issue lies in the susceptibility of commercially available lithium hexafluorophosphate (LiPF6) salts to hydrolysis caused by trace amounts of water, producing corrosive hydrofluoric acid. This leads to the dissolution of the cathode metal and damage to the SEI film on the anode. Specifically: High-energy-density lithium-ion batteries commonly employ a nickel-rich ternary cathode with a nickel content of no less than 0.8% and a silicon-based anode. However, the nickel-rich cathode has high residual alkali and strong oxidizing properties, while the silicon-based anode experiences significant volume changes during lithium insertion / extraction. Both place high demands on the stability of the electrolyte interface. Currently, commercially available lithium hexafluorophosphate (LiPF6) is sensitive to trace amounts of water, hydrolyzing to form hydrofluoric acid. Hydrofluoric acid corrodes the cathode and damages the solid electrolyte interface film of the anode, causing transition metal dissolution, increased gas production, and accelerated capacity decay. While conventional electrolytes can improve the interface by adding film-forming agents such as vinylene carbonate and fluoroethylene carbonate, these additives have limited dehydration and deacidification capabilities, failing to inhibit LiPF6 hydrolysis at its source. Although carboxylic acid ester solvents have low viscosity and high conductivity, which is beneficial for fast charging, they are easily oxidized and decomposed at high voltages and temperatures, leading to decreased cycle stability when used alone. Cyclic carbonates can stabilize the solvation structure of lithium salts, but excessive amounts increase viscosity and deteriorate fast-charging performance.
[0003] Existing electrolytes cannot simultaneously meet the requirements of water and acid removal, high voltage stability, fast charging, and long cycle life. Therefore, it is crucial to develop new electrolytes that combine efficient water and acid removal functions. Summary of the Invention
[0004] This invention discloses an interface-stabilized electrolyte for high-nickel / silicon-based batteries and its application, belonging to the field of lithium-ion battery electrolyte technology; it solves the problems of HF corrosion and interface instability caused by moisture in high-nickel / silicon-based battery systems, and improves battery cycle performance and safety.
[0005] An interface-stabilized electrolyte for high-nickel silicon-based batteries, characterized in that, based on the total mass of the electrolyte (100%), the weight percentages of each component are as follows: Lithium salts: 10%–22%; Silicon-based compound additives: 0.02%–0.3%; Polysulfate additives: 0.05%–3%; Functional additives: 0.1%–12%; The remainder is organic solvent; The structure of the silicon-based compound additive is as follows: In the structural formula, A, B, and C are each independently selected from fluorine atoms and C1-C4 straight-chain or branched alkyl groups, wherein the alkyl group is methyl or ethyl; D is a divalent linking group between two carbonyl carbon atoms, and D is selected from C2-C4 alkylene, C2-C4 alkenyl, C6-C10 aryl, C3-C6 alicyclic hydrocarbon, and C3-C6 cycloalkenyl, including ethylene, vinyl, phenyl, and cyclobutyl; specific exemplary compounds of the silicon-based compounds of the present invention are as follows:
[0006] Example 1 Example 2 Example 3 Example 4
[0007] Example 5 Example 6 Example 7 Example 8 The organic solvent contains 5%–35% cyclic carbonates, 25%–60% chain carbonates, and 10%–40% carboxylic acid esters, with the cyclic carbonates, chain carbonates, and carboxylic acid esters accounting for 100% of the total mass of the organic solvent.
[0008] Preferably, the silicon-based compound additive is 0.02% to 0.3%, and its content in the electrolyte is denoted as a; the polysulfate additive is selected from at least one of vinyl sulfate, propylene sulfate, and vinyl disulfate, wherein the content of the polysulfate in the electrolyte is denoted as b, and a and b satisfy 0.03≤a / b≤0.4.
[0009] Preferably, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium oxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, or lithium bis(trifluoromethylsulfonyl)imide; the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.8 mol / L.
[0010] Preferably, the carboxylic acid ester solvent is selected from at least one of propyl propionate, ethyl propionate, methyl propionate, ethyl acetate, and methyl acetate, wherein the carboxylic acid ester accounts for 10% to 40% of the total mass of the organic solvent, denoted as c, and a and c satisfy 0.001 ≤ a / c ≤ 0.02. Preferably, the cyclic carbonate solvent is selected from at least one of ethylene carbonate and propylene carbonate, wherein the cyclic carbonate accounts for 5% to 35% of the total mass of the organic solvent, denoted as d, and a and d satisfy 0.003≤a / d≤0.04.
[0011] Preferably, the chain carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0012] Preferably, the content of silicon-based compound additive is a, the content of carboxylic acid ester is c, and the content of cyclic carbonate is d, wherein a, c, and d satisfy 0.01≤100a×d / c≤0.4.
[0013] Preferably, the functional additives include at least one of vinylene carbonate, fluorovinyl carbonate, 1,3-propanesulfonate lactone, succinate, or adiponitrile.
[0014] Preferably, the method for preparing an interface-stabilized electrolyte for high-nickel silicon-based batteries includes the following steps: S1. Under inert atmosphere, dew point ≤ -35℃, and water content ≤ 5ppm, cyclic carbonate, chain carbonate and carboxylic acid ester are mixed according to the formula, and stirred at 15℃~35℃ and stirring speed 200r / min~500r / min for 20min~40min to obtain mixed solvent. S2. Add lithium salt to the mixed solvent and stir at 20℃~40℃ for 30min~90min until dissolved. Then cool to 10℃~25℃ to obtain lithium salt solution. S3. First, add the silicon-based compound additive shown in structural formula 1 to the lithium salt solution and stir for 15 min to 30 min. Then, add the polysulfate ester additive and stir for 30 min to 60 min. Finally, add other optional functional additives and stir for 15 min to 40 min. S4. Filter the above solution through a 0.22μm to 0.5μm filter membrane and degas it for 10 min to 30 min at 20℃ to 30℃ and a vacuum of -0.08MPa to -0.1MPa to obtain an interface-stabilized electrolyte for high-nickel silicon-based batteries.
[0015] Preferably, a lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte is an application of a lithium-ion battery electrolyte; the thickness of the positive electrode is 50μm~90μm, the separator is a ceramic / aramid coated separator with a thickness of 7μm~20μm; the lithium-ion battery is a high-nickel / silicon-based high-energy-density battery, the positive electrode is a nickel-rich ternary positive electrode with a nickel content ≥0.8%, and the negative electrode is a silicon-based negative electrode, silicon oxide, or silicon-carbon composite.
[0016] The beneficial technical effects of this invention are as follows: The silicon-based compound additive effectively captures trace amounts of water and HF in the electrolyte, inhibiting lithium salt hydrolysis side reactions and acid corrosion. This substance also readily forms a stable interface film on the electrode surface, not only inhibiting the dissolution of high-nickel cathode metal but also suppressing damage to the interface protective film caused by the expansion of the silicon anode, thus improving battery cycle stability and safety. The silicon-based additive and carboxylic acid ester solvent exhibit excellent synergistic effects, inhibiting high-pressure oxidative decomposition of carboxylic acid esters while retaining their high conductivity advantage, balancing battery fast-charging performance and electrolyte high-pressure stability. The cyclic carbonate constructs a stable lithium salt solvation structure, and the silicon-based additive synergistically optimizes the system interface environment, broadens the electrolyte electrochemical window, and improves thermal stability, making it suitable for high-voltage, wide-temperature-range operating scenarios of high-nickel / silicon-based batteries. By limiting the ratio range of silicon-based additives and various solvents, the interfacial transport resistance can be reduced, and the cycle and fast-charging performance can be improved simultaneously while ensuring high energy density. The polysulfate and silicon-based components work together to form a sulfur- and nitrogen-containing composite interfacial protective film at the positive and negative electrode interfaces, which reduces the charge impedance of the interface and further improves the interface stability, thereby improving the battery cycle life and fast-charging capability. Detailed Implementation
[0017] The technical solution of the present invention will be described in detail below with reference to embodiments. The following is an exemplary description of the present invention and does not constitute a limitation on the scope of protection of the present invention. The specific implementation process includes: Example 1 of specific implementation process: A method for preparing an interface-stabilized electrolyte for high-nickel silicon-based batteries includes the following steps: S1. Under inert atmosphere, dew point ≤ -35℃, and water content ≤ 5ppm, cyclic carbonate, chain carbonate and carboxylic acid ester are mixed according to the formula, and stirred at 30℃ and stirring speed 400r / min for 30min to obtain mixed solvent. S2. Add lithium salt to the mixed solvent, stir at 30°C for 60 min until dissolved, and then cool to 20°C to obtain lithium salt solution; S3. First, add the silicon-based compound additive shown in structural formula 1 to the lithium salt solution and stir for 20 minutes. Then, add the polysulfate ester additive and stir for 45 minutes. Finally, add other optional functional additives and stir for 30 minutes. S4. Filter the above solution through a 0.4μm filter membrane and degas at 25℃ and a vacuum of -0.09MPa for 20 min to obtain an interface-stabilized electrolyte for high-nickel silicon-based batteries.
[0018] Example 2 of the specific implementation process: A method for preparing an interface-stabilized electrolyte for high-nickel silicon-based batteries includes the following steps: S1. Under inert atmosphere, dew point ≤ -35℃, and water content ≤ 5ppm, cyclic carbonate, chain carbonate and carboxylic acid ester are mixed according to the formula, and stirred at 15℃ and stirring speed 200r / min for 20min to obtain a mixed solvent. S2. Add lithium salt to the mixed solvent, stir at 20°C for 90 min until dissolved, and then cool to 10°C to obtain lithium salt solution; S3. First, add the silicon-based compound additive shown in structural formula 1 to the lithium salt solution and stir for 15 min. Then, add the polysulfate ester additive and stir for 30 min. Finally, add other optional functional additives and stir for 15 min. S4. Filter the above solution through a 0.22μm filter membrane and degas at 30℃ and a vacuum of -0.1MPa for 10 min to obtain an interface-stabilized electrolyte for high-nickel silicon-based batteries.
[0019] Example 3 of the specific implementation process: A method for preparing an interface-stabilized electrolyte for high-nickel silicon-based batteries includes the following steps: S1. Under inert atmosphere, dew point ≤ -35℃, and water content ≤ 5ppm, cyclic carbonate, chain carbonate and carboxylic acid ester are mixed according to the formula, and stirred at 35℃ and stirring speed 500r / min for 20min to obtain mixed solvent. S2. Add lithium salt to the mixed solvent, stir at 40°C for 30 min until dissolved, and then cool to 25°C to obtain lithium salt solution; S3. First, add the silicon-based compound additive shown in structural formula 1 to the lithium salt solution and stir for 15 min. Then, add the polysulfate ester additive and stir for 60 min. Finally, add other optional functional additives and stir for 15 min. S4. Filter the above solution through a 0.5μm filter membrane and degas at 20℃ and a vacuum of -0.08MPa for 30 min to obtain an interface-stabilized electrolyte for high-nickel silicon-based batteries.
[0020] In the experimental tests, the water content and acidity of the electrolyte were tested according to the methods specified in GB / T 19282-2014 "Lithium-ion Battery Electrolytes". The water content was determined by the Karl Fischer coulometric method, and the acidity was measured by acid-base titration and expressed as hydrogen fluoride.
[0021] The cell cycle life test adopts the constant current charge and discharge method in GB / T 31484-2015 "Requirements and Test Methods for Cycle Life of Power Batteries for Electric Vehicles". The cells are cycled at 45℃ and 25℃ with 1C constant current charging and 1C constant current discharging respectively. The number of cycles is recorded when the discharge capacity decays to 80% of the initial nominal capacity.
[0022] Fast charging performance testing adopted the rate performance testing approach in GB / T 31486-2015 "Electrical Performance Requirements and Test Methods for Power Batteries for Electric Vehicles". The capacity was first calibrated by 0.2C discharge at 25℃, followed by 1C constant current charging and 2C constant current discharging. The percentage of 2C discharge capacity to 0.2C discharge capacity was calculated to obtain the fast charging capacity retention rate. The basic electrolyte was EC:EMC=3:7 + 1M LiPF6, i.e., ethylene carbonate to methyl ethyl carbonate mass ratio 3:7, and the lithium salt lithium hexafluorophosphate concentration was 1 mol / L.
[0023] Experimental Test Example 1: The purpose of this experiment was to investigate the effect of different amounts of silicon-based compounds added on the moisture and acidity of the electrolyte. Following the specific implementation process in Examples 1-3, the basic electrolyte was prepared with the only difference being the addition of different mass percentages of the silicon-based compound shown in Structural Formula 1. The silicon-based compound is an example compound where D is ethylene and A, B, and C are all methyl groups. The comparative example is a basic electrolyte without any silicon-based compound added. The moisture and acidity of each sample were measured after standing at 25°C for 24 hours. The results are as follows: Table 1 compares the effects of different amounts of silicon-based compound additives on the moisture and acidity of the electrolyte.
[0024] The test results show that, within the dosage range specified in this invention, the silicon-based compound can significantly reduce the moisture and acidity of the electrolyte. This compound can capture trace amounts of moisture in the electrolyte and HF generated by lithium salt hydrolysis, inhibit the continuous hydrolysis of lithium salt, reduce acid corrosion of the system, and effectively improve the basic stability and storage stability of the electrolyte.
[0025] Experimental Test Example 2: The purpose of this experiment was to investigate the effects of different ratios of silicon-based compounds and carboxylic acid ester composite systems on the cycle performance and fast-charging performance of the battery cells. Based on the specific implementation process in Examples 1-3, the basic electrolyte was prepared with a fixed silicon-based compound content of 0.1%. Different amounts of propyl propionate were added as a carboxylic acid ester solvent, and the ratio of cyclic carbonates to chain carbonates was adjusted accordingly. All samples were configured as pouch cells, with a nickel-rich ternary material (0.88% nickel content) as the positive electrode, a silicon-carbon composite negative electrode, and a ceramic-coated separator. Each battery underwent 1C / 1C cycle testing at 45°C and 25°C, and the 2C fast-charging capacity retention rate was also tested. The results are as follows: Table 2 compares the effects of different amounts of silicon-based compounds and carboxylic acid ester solvents on cell performance.
[0026] The test results show that, within the dosage range specified in this invention, carboxylic acid ester solvents can reduce electrolyte resistance and increase lithium-ion transport rate, which is beneficial for fast charging. However, their electrode interface stability is poor, and they are prone to interface decomposition and by-product generation when used alone, leading to cycle degradation. Within the a / c ratio range specified in this invention, silicon-based compounds and carboxylic acid esters form a good synergy. The silicon-based compounds form a stable protective film at the electrode interface, inhibiting the oxidative decomposition of carboxylic acid esters, while retaining the advantages of low impedance and high mass transfer of carboxylic acid esters. The cell exhibits a better 2C fast charging capacity retention rate, significantly improving the battery's high-voltage cycle and fast charging performance. When the ratio exceeds the range of this invention, not only does the cycle life decrease, but the fast charging capacity retention rate also deteriorates simultaneously.
[0027] Experimental Test Example 3: The purpose of this experiment was to investigate the effects of different ratios of silicon-based compounds and cyclic carbonates on the cycle and fast-charging performance of the battery cell. Based on the specific implementation process in Examples 1-3, the basic electrolyte was prepared with a fixed silicon-based compound content of 0.1%. The content of ethylene carbonate in the organic solvent was adjusted, with the remainder supplemented by methyl ethyl carbonate. Carboxylic acid esters were not added initially. After assembling the batteries, the cycle life at 45℃ and 25℃ and the 2C fast-charging retention rate were tested for each sample. The results are as follows: Table 3 compares the effects of different amounts of silicon-based compounds and cyclic carbonate solvents on cell performance.
[0028] The test results, as shown in the table above, verify the impact of different ratios of silicon-based compounds and cyclic carbonates on the cell's cycle and fast-charging performance. Cyclic carbonates are used to construct a stable lithium salt solvation structure, ensuring sufficient lithium salt dissociation. However, there is an optimal range for their content: excessive content increases electrolyte viscosity, raises the negative electrode interface impedance, and deteriorates fast-charging capability; excessive content leads to a lack of negative electrode film-forming components, resulting in poor SEI film quality. This invention, by limiting the a / d ratio, effectively optimizes the solvation structure, improves the interface state, and reduces the interface impedance of silicon-based compounds. While improving the battery's wide-temperature cycle performance, the 2C fast-charging capacity retention rate of the cell is significantly improved.
[0029] Experimental Test Example 4: The purpose of this experiment was to investigate the synergistic regulatory effect of a ternary composite system of silicon-based compounds, cyclic carbonates, and carboxylic acid esters on the overall cycle and fast-charging performance of the battery cell. Based on the specific implementation process in Examples 1-3, the basic electrolyte was prepared by adding silicon-based compounds, ethylene carbonate, and ethyl propionate as needed, with ethyl methyl carbonate as the remaining solvent, maintaining a lithium salt concentration of 1M. Each sample was assembled into a battery and then tested. The results are as follows: Table 4 compares the effects of different silicon-based compounds, cyclic carbonates, and carboxylic acid ester solvent contents on cell performance.
[0030] The test results, as shown in the table above, verify the synergistic regulatory effect of the ternary compound system of silicon-based compound, cyclic carbonate, and carboxylic acid ester on the overall performance of cell cycling and fast charging. Within the specified ratio range of this invention, the three components exhibit a significant synergistic effect: the cyclic carbonate stabilizes the lithium salt solvation structure and improves the electrochemical stability of the electrolyte; the carboxylic acid ester reduces system impedance and improves lithium-ion transport efficiency; and the silicon-based compound constructs a dense and stable interfacial film on the positive and negative electrode surfaces, inhibiting electrolyte decomposition, high-nickel positive electrode metal dissolution, and silicon negative electrode interface damage. The coupling and optimization of the system interface and solvation structure overcomes the performance defects of single components, not only improving cycle life at room temperature and high temperature but also significantly enhancing the 2C fast charging capacity retention rate, making it suitable for the demanding operating conditions of high-nickel / silicon-based negative electrode batteries.
[0031] Experimental Test Example 5: The purpose of this experiment is to investigate the effects of different ratios of silicon-based compounds and polyvinyl sulfate compounds on the cycle performance and fast-charging performance of the battery cell. Based on the specific implementation process in Examples 1-3, the basic electrolyte was prepared with a fixed silicon-based compound content of 0.1%, and different amounts of vinyl sulfate were added as polyvinyl sulfate additives. The test results are as follows: Table 5 compares the effects of different amounts of silicon-based compounds and polysulfates on cell performance.
[0032] The test results, as shown in the table above, verify the impact of different ratios of silicon-based compounds and polysulfate compounds on the cell's cycle performance and fast-charging performance. This invention, by limiting the ratio of the two compounds, synergistically constructs a sulfur- and nitrogen-containing composite interface protective film at the positive and negative electrode interfaces, reducing interfacial charge transfer resistance, improving interface stability, enhancing battery cycle life, and simultaneously improving 2C fast-charging capacity retention. Insufficient addition of polysulfate compounds fails to achieve the synergistic effect, while excessive addition induces side reactions, increases interfacial resistance, and causes a simultaneous decline in both cycle performance and fast-charging capability.
[0033] The silicon-based compound additive of this invention contains silicon-nitrogen bonds, and the D group between the two carbonyl groups is an unsaturated or cyclic structure such as alkylene, alkenyl, or aryl. The silicon-nitrogen bond is highly reactive to water and hydrogen fluoride, preferentially undergoing hydrolysis or fluorination reactions. After cleavage, it generates silanol groups or silicon-fluorine bonds, releasing cyclic imide fragments, thereby irreversibly consuming proton impurities in the system and inhibiting the hydrolysis and acid corrosion of lithium hexafluorophosphate. The unsaturated bonds of the D groups can participate in electrochemical polymerization or ring-opening reactions on the electrode surface, forming a silicon- and nitrogen-containing interfacial film. This film is dense and flexible, capable of covering the surface of the high-nickel cathode, reducing metal dissolution, and simultaneously adapting to volume changes in the silicon anode, reducing the rupture of the solid electrolyte interfacial film. When compounded with carboxylic esters, silicon-based additives remove acidic substances, reduce the oxidative decomposition of carboxylic esters under high pressure, retain their low viscosity and high conductivity, and improve fast charging performance. When compounded with cyclic carbonates, cyclic carbonates maintain lithium salt dissociation, while silicon-based compounds optimize the interface state, reduce interface impedance, and broaden the electrochemical window. When compounded with polysulfate esters, sulfur-containing species and silicon-containing species co-deposit to form a composite interface film, reducing interfacial charge transfer impedance.
[0034] Therefore, compared with existing technologies, the electrolyte of this invention can simultaneously achieve dehydration and deacidification, interface stabilization, and fast charging improvement in high-nickel silicon-based systems, exhibiting significant overall advantages. In the field of new energy vehicles, it can be used in high-nickel ternary / silicon-based negative electrode power batteries to improve driving range, fast charging capability, and high-temperature safety. In the field of consumer electronics, it can be used in high-energy-density polymer lithium batteries for smartphones, drones, etc., to improve cycle life and anti-expansion performance. In the field of energy storage power stations, it can be used in long-life energy storage cells to enhance chemical stability over a wide temperature range. In the field of electrolyte manufacturing, it can be directly formulated as a functional additive component to produce high-performance lithium-ion battery electrolytes.
Claims
1. An interface-stabilized electrolyte for high-nickel silicon-based batteries, characterized in that, Based on the total mass of the electrolyte being 100%, the weight percentage of each component is as follows: Lithium salts: 10%–22%; Silicon-based compound additives: 0.02%–0.3%; Polysulfate additives: 0.05%–3%; Functional additives: 0.1%–12%; The remainder is organic solvent; The structure of the silicon-based compound additive is as follows: In the structural formula, A, B, and C are each independently selected from fluorine atoms, C1-C4 straight-chain or branched alkyl groups, wherein the alkyl group is methyl or ethyl; D is a divalent linking group between two carbonyl carbon atoms, and D is selected from C2-C4 alkylene, C2-C4 alkenyl, C6 ... 10 Aryl, C3-C6 alicyclic hydrocarbon, and C3-C6 cycloalkenyl, including ethylene, vinyl, phenyl, and cyclobutyl; The organic solvent contains 5%–35% cyclic carbonates, 25%–60% chain carbonates, and 10%–40% carboxylic acid esters, and the sum of cyclic carbonates, chain carbonates, and carboxylic acid esters accounts for 100% of the total mass of the organic solvent.
2. The interface-stabilized electrolyte for high-nickel silicon-based batteries according to claim 1, characterized in that, The silicon-based compound additive shown is 0.02% to 0.3%, and its content in the electrolyte is denoted as a; the polysulfate additive is selected from at least one of vinyl sulfate, propylene sulfate, and vinyl disulfate, wherein the content of the polysulfate in the electrolyte is denoted as b, and a and b satisfy 0.03≤a / b≤0.
4.
3. The interface-stabilized electrolyte for high-nickel silicon-based batteries according to claim 2, characterized in that, The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium oxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, or lithium bis(trifluoromethylsulfonyl)imide; the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.8 mol / L.
4. The interface-stabilized electrolyte for high-nickel silicon-based batteries according to claim 3, characterized in that, The carboxylic acid ester solvent is selected from at least one of propyl propionate, ethyl propionate, methyl propionate, ethyl acetate, and methyl acetate, wherein the carboxylic acid ester accounts for 10% to 40% of the total mass of the organic solvent, denoted as c, and a and c satisfy 0.001≤a / c≤0.
02.
5. The interface-stabilized electrolyte for high-nickel silicon-based batteries according to claim 4, characterized in that, The cyclic carbonate solvent is selected from at least one of ethylene carbonate and propylene carbonate, wherein the cyclic carbonate accounts for 5% to 35% of the total mass of the organic solvent, denoted as d, and a and d satisfy 0.003≤a / d≤0.
04.
6. The interface-stabilized electrolyte for high-nickel silicon-based batteries according to claim 5, characterized in that, The chain carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate.
7. The interface-stabilized electrolyte for high-nickel silicon-based batteries according to claim 6, characterized in that, The content of silicon-based compound additive is a, the content of carboxylic acid ester is c, and the content of cyclic carbonate is d, wherein a, c and d satisfy 0.01≤100a×d / c≤0.
4.
8. The interface-stabilized electrolyte for high-nickel silicon-based batteries according to claim 7, characterized in that, Functional additives include at least one of vinylene carbonate, fluorovinyl carbonate, 1,3-propanesulfonate lactone, succinate, or adiponitrile.
9. The interface-stabilized electrolyte for high-nickel silicon-based batteries according to claim 8, characterized in that, Its preparation method includes the following steps: S1. Under inert atmosphere, dew point ≤ -35℃, and water content ≤ 5ppm, cyclic carbonate, chain carbonate and carboxylic acid ester are mixed according to the formula, and stirred at 15℃~35℃ and stirring speed 200r / min~500r / min for 20min~40min to obtain mixed solvent. S2. Add lithium salt to the mixed solvent and stir at 20℃~40℃ for 30min~90min until dissolved. Then cool to 10℃~25℃ to obtain lithium salt solution. S3. First, add the silicon-based compound additive shown in structural formula 1 to the lithium salt solution and stir for 15 min to 30 min. Then, add the polysulfate ester additive and stir for 30 min to 60 min. Finally, add other optional functional additives and stir for 15 min to 40 min. S4. Filter the above solution through a 0.22μm to 0.5μm filter membrane and degas it for 10 min to 30 min at 20℃ to 30℃ and a vacuum of -0.08MPa to -0.1MPa to obtain an interface-stabilized electrolyte for high-nickel silicon-based batteries.
10. A lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The electrolyte is the lithium-ion battery electrolyte according to any one of claims 1 to 9; the thickness of the positive electrode sheet is 50μm to 90μm, and the separator is a ceramic / aramid coated separator with a thickness of 7μm to 20μm; the lithium-ion battery is a high-nickel / silicon-based high-energy-density battery, the positive electrode is a nickel-rich ternary positive electrode with a nickel content ≥0.8%, and the negative electrode is a silicon-based negative electrode, silicon oxide, or silicon-carbon composite.